Assessment of groundwater availability from recession flows and instream flow requirements of rivers in South Africa - Ebrahim, Girma Yimer; Villholth, Karen G. (Water Research Commission, 2015)
Groundwater is an important resource for multiple uses in South Africa. However, setting limits to its sustainable abstraction while assuring basic human needs is a must. Due to prevalent data scarcity related to groundwater replenishment, which is the traditional basis for estimating groundwater availability, the present report presents a novel method for determining allocatable groundwater in quaternary catchment through information on streamflows. Using established methodologies for assessing baseflows, recession flows, and instream ecological flow requirements, the methodology develops a combined stepwise methodology to determine annual groundwater storage volumes in the catchments using linear reservoir theory, essentially linking low flows proportionally to upstream groundwater storages. The approach was trialled for twenty-one perennial and relatively undisturbed quaternary catchments with long-term and good streamflow records. Using the Desktop Reserve Model to estimate instream ecological flow requirements of the streams and equating these with ecological groundwater reserve, excess baseflows were converted into groundwater storages on an annual basis. Results show that groundwater development potential exists in nineteen of the catchments, with upper limits to allocatable groundwater volumes ranging from 0.01 to 1.58 MCM/yr over the catchments. With a secured availability of these volumes 75% of the years, variability between years is assumed to be manageable. A significant (R2 = 0.86) correlation between baseflow index and the drainage time scale for the catchments underscored the physical basis of the methodology and also enables the reduction of the procedure by one step, omitting recession flow analysis. The method serves as an important complementary tool for the assessment of the groundwater part of the Reserve and the groundwater directed measures.